DIABETIC EMERGENCIES: COMBINED HYPEROSMOLAR HYPERGLYCEMIC STATE AND DIABETIC KETOACIDOSIS - Doydora , Josephine Khaye; Patriana , Emilia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE There is no currently accepted definition for patients presenting with a combination of hyperglycemic hyperosmolar state and diabetic ketoacidosis. An overlap of both entities is associated with greater mortality thanisolated HHS or DKA. We describe a case of a 69-yearold Filipino male with type 2 diabetes and dementia who presented with mixed HHS and DKA. The patient was tachycardic and tachypneic with dry oral mucosa and poor skin turgor associated with metabolic acidosis, ketonuria, elevated osmolarity, and anion gap. Non-adherence to insulin with concomitant atypical antipsychotic medication use may have precipitated the condition. Fluid repletion, insulin therapy, and correction of hyperosmolarity and acidosis resulted in the recovery of the patient without complications. This case highlighted the importance of defining management strategies for mixed types of diabetic emergencies to prevent mortality and morbidity.